Uromyces acori (Uredinales) Penyebab Nekrosis pada Daun Tanaman Jeringau (Acorus calamus) di Indonesia - Dono Wahyuno; Marlina Puspita Sari; Dini Florina (Jurnal Fitopatologi Indonesia, 2020)
Uromyces acori (Uredinales) A Causal Agent of Rust Disease of Sweet Flag (Acorus calamus) in Indonesia In Indonesia, an asexual state of a rust fungus namely Uredo acori has been considered as the causal agent rust disease of the sweet flag. No report according sexual state is available in Indonesia. The objectives of the present study are confirming the fungal identity morphologically and determine its optimal germinating temperature. An artificial inoculation was conducted by dusting the urediniospore onto detached leaves of sweet flag. Only leaves showed uredinia were selected. The tip bases of the leaves were dipped into a 4% sucrose solution, incubated in a room condition at 25 °C for inducing telial state with teliospore formations. Based on morphological characters of the teliospore and urediniospore, the rust fungus of sweet flag was identified as Uromyces acori. The fungus is germinating optimally at 25 °C.